1989
DOI: 10.1111/j.1399-3054.1989.tb05486.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of ethylene, ACC, MACC, ABA and proline as indicators of cold hardening and frost resistance in winter wheat

Abstract: Machackova, L, Hanisova, A, and Krekule, J, 1989, Levels of ethylene, ACC. MACC, ABA and proline as indicators of cold hardening and fro.st resistance in winter wheat. Plant, 76;[603][604][605][606][607] Changes in ethylene production and in the contents of 1-aminoeyelopropane-l-carbt>xylic acid (ACC), l-(malonylamino)-cyclopropane-l-carboxylic aeid (MACC), abscisic aeid (ABA) and L-proline were detennined after 40 days of cold hardening at 4°C in three wheat cultivars differing in frost resistance, Prolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…In addition, ethylene production decreased sharply at low temperatures and rose rapidly (within 1 d) after a return to normal temperatures in winter wheat (Triticum aestivum) and dwarf bean (Phaseolus vulgaris) (Field, 1984;Machá ccková et al, 1989). Another study from mung bean (Vigna radiata) seedlings showed that improved tolerance was associated with suppression of ethylene biosynthesis (Collins et al, 1995).…”
Section: Ethylene Signaling Plays An Important Role In Cold Stress Simentioning
confidence: 99%
“…In addition, ethylene production decreased sharply at low temperatures and rose rapidly (within 1 d) after a return to normal temperatures in winter wheat (Triticum aestivum) and dwarf bean (Phaseolus vulgaris) (Field, 1984;Machá ccková et al, 1989). Another study from mung bean (Vigna radiata) seedlings showed that improved tolerance was associated with suppression of ethylene biosynthesis (Collins et al, 1995).…”
Section: Ethylene Signaling Plays An Important Role In Cold Stress Simentioning
confidence: 99%
“…Acclimation of a number of plant species to low temperatures was found to be associated with elevation in the endogenous ABA levels [3][4][5][6], and exogenous application of ABA-induced increased freezing and chilling tolerance [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of PKABAl mRNA may be part of the initial stress response to environmental signals mediated by ABA that ultimately result in the accumulation of osmoprotectants~ ABA increases in plants exposed to severa1 types of environmental stress and acts as a signal, although tertainly not the only signal, to promote tissue acclimation to stress (reviewed by Chandler and Robertson, 1994). Elevated ABA levels have been correlated with increased tolerance to dehydration (Bartels et al, 1990) and sometimes to cold (Machackova et al, 1989;Lee et al, 1993), osmotic, and salt (Singh et al, 1987) stress. ABA-deficient mutants provide genetic evidente for the role of ABA in the acclimation process to stress (reviewed by Reid, 1990).…”
mentioning
confidence: 99%